The Interaction Between Pulmonary Fibrosis and COVID-19 and the Application of Related Anti-Fibrotic Drugs - Shen, Hao; Zhang, Nu; Liu, Yuqing; Yang, Xuerong; He, Yuanyuan; Li, Qi; Shen, Xiaoyan; Zhu, Yulian; Yang, Yong (Frontiers in Pharmacology, 2022)
COVID-19 is a highly contagious respiratory disease, which mainly affects the lungs. Critically ill patients are easily complicated by cytokine storms, acute respiratory distress syndrome (ARDS), and respiratory failure, which seriously threaten their lives. Pulmonary fibrosis (PF) is a common interstitial lung disease, and its pathogenesis may involve the participation of a variety of immune cells and inflammatory factors. Current studies have shown that patients with COVID-19 may be complicated by pulmonary fibrosis, and patients with pulmonary fibrosis may also be at higher risk of contracting COVID-19 than healthy people. Pulmonary fibrosis is an important risk factor leading to the aggravation of COVID-19 disease. COVID-19 complicated by cytokine storm and ARDS mechanism pathways are similar to the pathogenesis of pulmonary fibrosis. The potential interaction between pulmonary fibrosis and COVID-19 can cause acute exacerbation of the patient’s condition, but the potential mechanism between the two has not been fully elucidated. Most of the drug treatment programs for COVID-19-related pulmonary fibrosis are currently formulated about the relevant guidelines for idiopathic pulmonary fibrosis (IPF), and there is no clear drug treatment program recommendation. This article aims to summarize the relevant mechanism pathways of COVID-19 and pulmonary fibrosis, explore the interrelationships and possible mechanisms, and discuss the value and risks of existing and potential COVID-19-related pulmonary fibrosis treatment drugs, to provide reference for anti-fibrosis treatment for patients.